Is Topic a Root Phenomenon? - Bianchi, Valentina; Frascarelli, Mara (IBERIA: An International Journal of Theoretical Linguistics, 2010)
In this paper we discuss the question of whether topics are necessarily restricted to root clauses. From an interface perspective, if topics affect the management of the conversational common ground (Reinhart 1981; Büring 2003; Krifka 2007), we expect them to appear in clauses endowed with illocutive force, implementing a conversational move (§ 2). This conclusion, however, is too general. Adopting the typology of topics by Frascarelli & Hinterhölzl (2007), we show (§ 3) that Familiar topics do not affect the conversational dynamics, and as expected, they are not restricted to root clauses. The English-Romance asymmetry in the distribution of topics (Haegeman 2004) is reduced to the lack of Familiar topics in English, as opposed to Romance. In § 4 we discuss English contrastive topics, showing that they have embedded interpretations in non-asserted complement clauses: we therefore sketch a semantic analysis which does not link contrastive topics to conversational strategies of inquiry. The only type of topic that complies with the root restriction is the Aboutness-Shift topic (§ 5): we suggest that it can be analysed as an independent speech act (cf. Krifka 2001). Finally, in § 6 we discuss «root-like» embedded clauses and offers a tentative solution for their quasi-assertive role.